Siponimod (BAF-312) Attenuates Perihemorrhagic Edema And Improves Survival in Experimental Intracerebral Hemorrhage. Issue 11 (November 2019) - Bobinger, Tobias; Manaenko, Anatol; Burkardt, Petra; Beuscher, Vanessa; Sprügel, Maximilian I.; Roeder, Sebastian S.; Bäuerle, Tobias; Seyler, Lisa; Nagel, Armin M.; Linker, Ralf A.; Engelhorn, Tobias; Dörfler, Arnd; et al.
Abstract : Background and Purpose—: Perihemorrhagic edema (PHE) is associated with poor outcome after intracerebral hemorrhage (ICH). Infiltration of immune cells is considered a major contributor of PHE. Recent studies suggest that immunomodulation via S1PR (sphingosine-1-phosphate receptor) modulators improve outcome in ICH. Siponimod, a selective modulator of sphingosine 1-phosphate receptors type 1 and type 5, demonstrated an excellent safety profile in a large study of patients with multiple sclerosis. Here, we investigated the impact of siponimod treatment on perihemorrhagic edema, neurological deficits, and survival in a mouse model of ICH. Methods—: ICH was induced by intracranial injection of 0.075 U of bacterial collagenase in 123 mice. Mice were randomly assigned to different treatment groups: vehicle, siponimod given as a single dosage 30 minutes after the operation or given 3× for 3 consecutive days starting 30 minutes after operation. The primary outcome of our study was evolution of PHE measured by magnetic resonance-imaging on T2-maps 72 hours after ICH, secondary outcomes included evolution of PHE 24 hours after ICH, survival and neurological deficits, as well as effects on circulating blood cells and body weight. Results—: Siponimod significantly reduced PHE measured by magnetic resonance imaging ( P =0.021) as well as wet-dry method ( P =0.04) 72 hours after ICH. Evaluation of PHE 24 hours after ICH showed a tendency toward attenuated brain edema in the low-dosage group ( P =0.08). Multiple treatments with siponimod significantly improved neurological deficits measured by Garcia Score ( P =0.03). Survival at day 10 was improved in mice treated with multiple dosages of siponimod ( P =0.037). Mice treated with siponimod showed a reduced weight loss after ICH ( P =0.036). Conclusions—: Siponimod (BAF-312) attenuated PHE after ICH, increased survival, and reduced ICH-induced sensorimotor deficits in our experimental ICH-model. Findings encourage further investigation of inflammatory modulators as well as the translation of BAF-312 to a human study of ICH patients. Abstract : Supplemental Digital Content is available in the text.